Extracellular Matrix from Porcine Small Intestinal Submucosa (SIS) as Immune Adjuvants - Aachoui, Youssef (Public Library of Science, 2011)
Porcine small intestinal submucosa (SIS) of Cook Biotech is licensed and widely used for tissue remodeling in humans. SIS was shown to be highly effective as an adjuvant in model studies with prostate and ovarian cancer vaccines. However, SIS adjuvanticity relative to alum, another important human-licensed adjuvant, has not yet been delineated in terms of activation of innate immunity via inflammasomes and boosting of antibody responses to soluble proteins and hapten-protein conjugates. We used ovalbumin, and a hapten-protein conjugate, phthalate-keyhole limpet hemocyanin. The evaluation of SIS was conducted in BALB/c and C57BL/6 mice using both intraperitoneal and subcutaneous routes. Inflammatory responses were studied by microarray profiling of chemokines and cytokines and by qPCR of inflammasomes-related genes. Results showed that SIS affected cytokine and chemokines microenvironments such as up-regulation of IL-4 and CD30-ligand and activation of chemotactic factors LIX and KC (neutrophil chemotactic factors), MCP-1 (monocytes chemotactic factors), MIP 1-α (macrophage chemotactic factor) and lymphotactin, as well as, growth factors like M-CSF. SIS also promoted gene expression of Nod-like receptors (NLR) and associated downstream effectors. However, in contrast to alum, SIS had no effects on pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) or NLRP3, but it appeared to promote both Th1 and Th2 responses under different conditions. Lastly, it was as effective as alum in engendering a lasting and specific antibody response, primarily of IgG1 type.